Design and Construction of a Portable Plastic Bottle and Gallon Shredding Machine Driven by a 4-Stroke Motor in Buran Village, Karanganyar - Sukmaji Indro cahyono; Syafruddin Arsyad; Kevin William Markus Simbolon; Muhammad Farhan (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
Buran Village in Karanganyar Regency faces challenges in managing household plastic waste, particularly used bottles and gallon jugs, due to limited shredding technology. Existing industrial-scale plastic shredders are generally very large, expensive, and require three-phase electricity, making them unsuitable for rural communities. Meanwhile, the manual methods and simple tools used by the community have proven inefficient and pose a risk of injury. This community service program aims to design and build a portable plastic shredder powered by a 4-stroke motorcycle as an appropriate technology solution for Buran Village. The implementation method includes identifying field problems, surveying user needs, conceptualizing and detailing designs, fabricating a prototype, and conducting initial performance tests. The result is a compact, portable shredder powered by a 125cc 4-stroke gasoline engine. The shredding mechanism uses three dynamic blades and one static blade capable of shredding plastic bottles and gallon jugs into 1–2 cm pieces on average. The machine is equipped with wheels and a handle for portability, as well as safety features such as a blade cover, a safety hopper, and a push lever. Trials demonstrated that the machine can continuously shred approximately 15 kg of PET waste per day, reducing waste volume by >80% at the source. Implementation and evaluation results indicated that the machine is easy to operate, independent of PLN electricity supply, and has the potential for widespread community replication using components commonly available in local workshops. Implementation of this technology in Buran Village is expected to improve the efficiency of plastic waste management, increase the economic value of waste for residents, and support efforts to reduce plastic pollution.